Peningkatan Kualitas Minyak Nilam Melalui Proses Adsorpsi Menggunakan Adsorben Γ-Alumina Dengan Sistem Flow - Wati, Nur Fitria Nella (Chemistry Department, Universitas Islam Indonesia, 2014)
Use of research studies have been carried γ - alumina as an adsorbent in improving the quality of patchouli oil carried through the adsorption process flow system. Quality improvement based on analysis of patchouli oil quality parameters in accordance with SNI 06-2385-2006 about patchouli oil. These parameters include color, specific gravity, refractive index, acid value, the metal content of iron (Fe) and patchouli alcohol levels. Fe concentration measurements carried out using AAS instrument, and patchouli alcohol content measurement using GC instrument. Variations in the use of γ - alumina adsorbents include weight variation is 5, 10, 15, 20 grams and variation of flow rate is 5 and 10 drops/min. Percent increase of patchouli alcohol occurred in the use of alumina as an adsorbent as much as 10 grams with a flow rate of 10 drops / min, increase of 27.6775 %. Moreover, it has the smallest Fe metal content is 11.2201 mg / kg. Colour, specific gravity, refractive index, and levels of metals Fe after adsorption have met the quality standard patchouli oil.